The local limit theorem of Delange in the Knopfmacher’s semigroup - Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2004)
An asymptotic formula of the mean value of multiplicative arithmetic function from the class Ma(G) with asymptotical expansion of the main term is obtained. In the present paper the local limit theorem of the H. Delange type is proved.